MENGHIDUPI IMAN KRISTEN YANG EKOLOGIS: SASI SEBAGAI PRAKTIK NYATA PERAWATAN CIPTAAN TUHAN - Nataninda Elsi Sola Gratia Sitompul (EIRENE (JURNAL ILMIAH TEOLOGI), 2025)
Rapid environmental change challenges Christians to express their faith through concrete actions in caring for all of God's creation. One way to do this is through Sasi, a form of local wisdom that regulates human relations with nature through rhythms of pause, respect, and exploitation of resources. This study aims to explain how the principles of Sasi can be understood as concrete practices of Christian faith that support the preservation of creation. The method used is a qualitative study based on theological, ethnographic, and ecological literature analysis, which is then combined descriptively and analytically to identify the intersection between cultural practices and Christian faith. The results show that Sasi is not only a social mechanism for maintaining environmental balance but can also be a space for active and rich theology. These findings confirm that the combination of Christian faith and local cultural values ​​has the potential to enrich models of care for creation, especially in the context of the escalating global ecological crisis. Thus, Sasi can be re-presented as a means of practicing faith applied to culture, faith, and comprehensive ecological concerns.